Application of blockchain technology in decentralized medical data security and privacy systems - Muhammad Fajar Dwi Setyoko; Muhamad Alief Firmansyah Putra; Muhammad Asghar Nazal; Remuz MB Kmurawak (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
In a time when both the quantity and number of medical records are growing, protecting medical information has taken on particular significance. Medical data security and privacy are still compromised by the current system, which leaves room for manipulation and data leaks. Prior research has suggested techniques to safeguard medical data using encrypted algorithms like Blowfish and Vigenere. Nonetheless, this study suggests blockchain technology as a remedy for medical data security and decentralized data protection solutions this work, we implement decentralized data protection and medical information security using smart contracts. Smart contracts are blockchain-encoded agreements that, under specific circumstances, guarantee the contract's execution. In medical information management, smart contracts are used to control how patients, physicians, and healthcare organizations may utilize information. By doing this, patients can consent to the secure and encrypted use of their medical data, guaranteeing that only individuals with the proper authorization can access the information. In this work, we leverage smart contracts and blockchain technology to enhance the security of medical data stored in hospitals or outpatient clinics. The study's findings demonstrate that the data held in blockchains is distributed among several nodes, making them resistant to malware attacks and making the technology hard to alter